Syntheses and crystal structures of the cerium-based coordination polymers poly[(acetic acid)bis(μ-5-carboxythiophene-2-carboxylato)bis(μ-thiophene-2,5-dicarboxylato)dicerium(III)] and poly[(μ-acetato)aqua(μ4-thiophene-2,5-dicarboxylato)cerium(III)] - Niklas Ruser; Christian Näther; Norbert Stock (Acta Crystallographica Section E: Crystallographic Communications)
The title compounds, [Ce2(C6H3SO4)2(C6H2SO4)2(CH3COOH)]n (1) and [Ce(CH3COO)(C6H2SO4)(H2O)]n (2) were synthesized by solvothermal reaction of Ce(NO3)3·6H2O with 2,5-thiophenedicarboxylic acid (H2TDC, C6H4SO4) and acetic acid in acetonitrile or ethanol/water, respectively. These compounds were obtained as single crystals among other crystalline phases. Both compounds belong to the family of three-dimensional coordination polymers. The asymmetric unit of 1 consists of two CeIII cations, two TDC2− dianions, two HTDC− anions and one acetic acid ligand, all of them located in general positions. The two CeIII cations are each coordinated by eight oxygen atoms in the form of distorted square antiprisms. These are bridged by carboxylate and carboxylic acid groups, forming mono-periodic hybrid inorganic building units (IBUs), which are connected into a three-dimensional network by the TDC2− and HTDC− ligands. Compound 2 has an asymmetric unit composed of one CeIII cation, one TDC2− dianion, one acetate anion and one water molecule in general positions. The cerium atom is eightfold coordinated by oxygen atoms. Edge-sharing CeO8 polyhedra form a dinuclear IBU (Ce2O14). This IBU is bridged by six TDC2− linkers to nine other IBUs, forming a three-dimensional framework. Both title compounds exhibit additional O—H...O hydrogen bonds. Powder X-ray diffraction shows that both compounds were not obtained as pure phases.